Stakeholder Engagement Models for Food Security Programs - Widodo, Dedyk Wahyu (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the stakeholder engagement model in the Food Security Program, particularly the Rice Planting Area Expansion Program (LTT) in Sidoarjo Regency, by identifying the roles, interaction patterns, and implementation challenges. A descriptive qualitative method was employed using purposive sampling involving the Department of Agriculture, Kodim 0816/Sidoarjo, Babinsa, agricultural extension officers, farmer groups, and individual farmers. Data were collected through in-depth interviews, field observations, and documentation, and were analyzed using the Miles, Huberman, and Saldaña model. The findings indicate that stakeholder involvement is collaborative and structured across three layers: policy, facilitation, and implementation. The government provides regulations and agricultural inputs, the military supports mobilization and planting discipline, while extension officers and farmers serve as technical implementers. Although the collaboration functions well, several challenges persist, including overlapping authority, limited technological adoption, land constraints, and suboptimal farmer capacity. The study implies the need for strengthened multisectoral coordination and enhanced human resource capacity in the agricultural sector.